Etos Kerja Manusia Bugis-Makassar sebagai Kritik terhadap Konsep Kerja dalam Budaya Kapitalisme Baru (Studi Filosofis atas Persoalan Pengangguran di Indonesia) - Sairah Z., Abdul Rokhmat (Jurnal Filsafat "WISDOM", 2011)
Various practices of the new capitalism implicitly exist in Indonesia. The practices are consumption tendencies and consequence of inequality in economy. This essay aims to explore work ethics of Bugis-Makassar people as a critique to work concept in the new capitalism and its relevance on unemployment problem in Indonesia. This essay shows that the unemployment problem in Indonesia is influenced by the work concept in the new capitalism. The new capitalism uses a culture as a tool to legitimate power and causes instability in labor system. Indonesia government must be able to face the new capitalism practices and return to a local wisdom to solve the unemployment problem.Â Keywords: work ethics, Bugis-Makasar people, work concept, new capitalism, unemployment problem, local wisdom.